Evaluating the performance of Vanaraja female line (PD-2) chicken for fertility, hatchability, body weight, shank length and keel length: Performance of Vanaraja female line (PD-2) - BALAKRISHNA REDDY G; CHINNI PREETAM V; GNANA PRAKASH G; RAJKUMAR U; SRINIVAS GURRAM; SAI REDDY; MOUNIKA THOTA (Indian Journal of Poultry Science, 2025)
The present study was aimed at evaluating the performance of Vanaraja female line (PD-2) chicken. Data collected on 3737 chicks, progeny of 50 sires and 250 dams produced in a pedigreed full sib mating at the Directorate of Poultry Research, Hyderabad in four hatches during 15th generation were utilized for the present investigation for estimating various parameters. The results indicated that the mean fertility was 83.57 percent. The overall mean hatchability percentage was 72.66 on Total Eggs Set (TES) and 86.95 on Fertile Eggs Set (FES). The mean fertility (83.57%) and hatchability (86.95 %) indicating the good reproduction and mothering of the PD-2 population. Highly significant (P